2004
DOI: 10.1016/s0277-9536(03)00261-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal literacy and health behavior: a Nepalese case study

Abstract: This article addresses the question of whether literacy could be mediating the relationships of schooling to maternal health behavior in populations undergoing demographic transition. Recent studies in which literacy was directly assessed suggest a literacy pathway to demographic change. The literacy skills of 167 urban and rural mothers of school-aged children in Lalitpur District of the Kathmandu Valley of Nepal were assessed by tests of reading comprehension, academic language proficiency, health media skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 9 publications
0
44
1
1
Order By: Relevance
“…Anand & Sen, 1997;LeVine et al, 2001;Maddox & Esposito, 2012;McTavish et al, 2010;Walter, 2010). Maternal education in the form of literacy has been recognized as a key pathway through which women's schooling effects reproduction and health behaviour (LeVine, LeVine, Rowe, & Schnell-Anzola, 2004). Moreover, literacy has been shown to provide wider social benefits both locally and in terms of greater social change (Gibson et al, 2004;Maddox & Esposito, 2012), as well as being the driving transformative force crucial to the restructuring of societies (Walter, 2010) …”
Section: Discussionmentioning
confidence: 99%
“…Anand & Sen, 1997;LeVine et al, 2001;Maddox & Esposito, 2012;McTavish et al, 2010;Walter, 2010). Maternal education in the form of literacy has been recognized as a key pathway through which women's schooling effects reproduction and health behaviour (LeVine, LeVine, Rowe, & Schnell-Anzola, 2004). Moreover, literacy has been shown to provide wider social benefits both locally and in terms of greater social change (Gibson et al, 2004;Maddox & Esposito, 2012), as well as being the driving transformative force crucial to the restructuring of societies (Walter, 2010) …”
Section: Discussionmentioning
confidence: 99%
“…La escolaridad de la madre en particular, determinante éste importante de comportamientos adecuados de higiene, mejores prácticas de cuidado del niño y mejores conocimientos en salud (39,40), se asocia en nuestro estudio con la presencia de parásitos intestinales patógenos (18). Así, las madres con menos años de primaria tienen mayor probabilidad de que sus hijos tengan poliparasitismo y algún tipo de helminto.…”
Section: Discussionunclassified
“…Research during the past 15 years has shown that those with limited health literacy skills have higher health care costs [1], use health care services more frequently or improperly [2][3][4], have poor understanding of chronic disease [4,5], have barriers to fully understanding one's health, illness and treatment [6], cannot adherent to medication regimens [7][8][9], affect health behaviors [10], tend to be less capable of properly caring for themselves [11,12], and influence health status.…”
Section: Introductionmentioning
confidence: 99%